War dances [compact disc, unabridged] - Alexie, Sherman, 1966- (Recorded Books, 2009)
As a 41-year-old man confronts his own mortality in this collection's title story, he recalls his Spokane Indian father's chilling death from alcoholism and diabetes. Another tale features an eccentric salesman pursuing a married woman from airport to airport. And then there's the film editor who sees nothing wrong with altering footage to fit preconceived views-- until he himself becomes the target of media distortion.